Stock market undervaluation of resource redeployability - Sakhartov, Arkadiy V. (Strategic Management Journal, 2018)
Research Summary : Stock market undervaluation of resources was often assumed to have strategic implications. Such undervaluation lets firms buy resources relatively cheaply, but it can also constrain resource deployment. This article shows that the option to redeploy a firm's resources to a new business can be undervalued in stock markets when investors face ambiguity about that option due to uniqueness of redeployment. The developed formal model derives conditions under which stock markets undervalue resources. Those conditions are summarized with an empirical operationalization that can be tested with a broad range of strategic implications. Besides, the model provides a more complete account of resource redeployability by demonstrating the redeployability paradox. The paradox highlights that some determinants of redeployability enhance undervaluation, while simultaneously increasing objective value of redeployable resources. Managerial Summary : Stock markets can systematically undervalue resources. On the one hand, such undervaluation creates a profitable opportunity for a firm that needs some resources for its growth and compares the option to buy stock in another firm, whose resource are undervalued, with the option to build those resources internally. On the other hand, such undervaluation poses limits to resource deployment strategies of the undervalued firm. When does such undervaluation occur? This study highlights one possible source for undervaluation, ambiguity that is faced by stock market investors about the option to redeploy a firm's resources to a new business. The study specifies conditions under which stock markets are more likely to undervalue resources. The understanding of those conditions can guide managers toward strategic opportunities.